PEMERIKSAAN HANDGRIP STRENGTH SEBAGAI EDUKASI DETEKSI DINI SARKOPENIA PADA USIA PRODUKTIF - Ruslim, Welly Hartono; Santoso, Alexander Halim; Destra, Edwin; Putra, Heri Yanto; Felicia, Ivana (AlMurtado Journal of Social Innovation and Community Service, 2025)
Decreased muscle strength is an early indicator of sarcopenia risk, which can begin during productive age. Handgrip strength measurement is a practical screening tool to assess muscle function, particularly in community settings. Low grip strength is often linked to inadequate daily protein intake. This community service activity was conducted at St. Francis of Assisi Church, South Jakarta, using the Plan–Do–Check–Act (PDCA) approach. Handgrip strength was measured using a digital dynamometer on both hands, and the results were categorized by gender. Educational sessions were provided on the importance of protein intake to support muscle health. A total of 65 participants were examined, most of whom were over 60 years old. Male participants showed higher average grip strength than females, with most women falling into the low muscle strength category. The findings suggest a potential decline in muscle function that may not yet be clinically apparent. Handgrip strength screening, combined with nutrition education, serves as an effective preventive strategy against muscle deterioration and can be implemented as an early community-level approach to sarcopenia prevention. Keywords: Handgrip Strength, Protein, Muscle, Sarcopenia, Education